Age-related macular degeneration and polypoidal choroidal vasculopathy in Asians. (July 2016) - Wong, Chee Wai; Yanagi, Yasuo; Lee, Won-Ki; Ogura, Yuichiro; Yeo, Ian; Wong, Tien Yin; Cheung, Chui Ming Gemmy
Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in elderly people globally. It is estimated that there will be more Asians with AMD than the rest of the world combined by 2050. In Asian populations, polypoidal choroidal vasculopathy (PCV) is a common subtype of exudative AMD, while choroidal neovascularization secondary to AMD (CNV-AMD) is the typical subtype in Western populations. The two subtypes share many common clinical features and risk factors, but also have different epidemiological and clinical characteristics, natural history and treatment outcomes that point to distinct pathophysiological processes. Recent research in the fields of genetics, proteomics and imaging has provided further clarification of differences between PCV and CNV-AMD. Importantly, these differences have manifested as disparity in response to intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) treatment between PCV and CNV-AMD, emphasizing the need for accurate diagnosis of PCV and in distinguishing PCV from CNV-AMD, particularly in Asian patients. Current clinical trials of intravitreal anti-VEGF therapy and photodynamic therapy will provide clearer perspectives of evidence-based management of PCV and may lead to paradigm shifts in therapeutic strategies away from those currently employed in the treatment of CNV-AMD. Further research is needed to clarify the relative contribution of specific pathways in inflammation, complement activation, extracellular matrix dysregulation, lipid metabolism and angiogenesis to the pathogenesis of PCV. Findings from this research, together with improved diagnostic technology and new therapeutics, will facilitate more optimal management of Asian AMD. Highlights: Genetic studies have uncovered a possible role of lipid metabolism in the pathogenesis of Asian AMD and PCV. Optical coherence tomographic angiography is a promising modality that may reduce the need for invasive tests in the future. Imaging biomarkers may help prognosticate and individualize treatment, further improving outcomes for patients with PCV.